2014
DOI: 10.1016/j.abb.2014.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a constitutive increase in myofilament Ca2+-sensitivity on Ca2+-fluxes and contraction of mouse heart ventricular myocytes

Abstract: Chronic increases in myofilament Ca2+-sensitivity in the heart are known to alter gene expression potentially modifying Ca2+-homeostasis and inducing arrhythmias. We tested age-dependent effects of a chronic increase in myofilament Ca2+-sensitivity on induction of altered alter gene expression and activity of Ca2+ transport systems in cardiac myocytes. Our approach was to determine the relative contributions of the major mechanisms responsible for restoring Ca2+ to basal levels in field stimulated ventricular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 60 publications
(72 reference statements)
1
8
0
Order By: Relevance
“…Furthermore, contribution of SERCA (61%) and NCX (31%) in hiPSC-CMs was not significantly different from adult rabbit-CMs (SERCA 60%, NCX 32%). As expected [29, 30], SERCA (89%) dominated in mouse-CMs. On the other hand, the relative contribution of non-NCX removal pathways was significantly larger in hiPSC-CMs (8-9%) compared to rabbit-CMs (4%) and mouse-CMs (2%).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Furthermore, contribution of SERCA (61%) and NCX (31%) in hiPSC-CMs was not significantly different from adult rabbit-CMs (SERCA 60%, NCX 32%). As expected [29, 30], SERCA (89%) dominated in mouse-CMs. On the other hand, the relative contribution of non-NCX removal pathways was significantly larger in hiPSC-CMs (8-9%) compared to rabbit-CMs (4%) and mouse-CMs (2%).…”
Section: Resultssupporting
confidence: 86%
“…Cytoplasmic Ca removal is mediated by three major pathways: (1) Ca uptake into the SR by the sarcoendoplasmic reticulum CaATPase (SERCA), (2) Ca efflux from the cell via the NCX, and (3), non-NCX non-SR mediated pathways such as plasma lemma Ca ATPase and mitochondria [25, 29]. The contribution of the individual Ca removal mechanisms has been studied extensively in non-human CMs [30, 31] but not yet in hiPSC-CMs. SR-independent Ca removal was tested by rapid caffeine application and was significantly slower in hiPSC-CMs compared to rabbit and mouse CMs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, it was shown that the expression of ssTnI in the mouse heart results in a leftward shift of the force-pCa relationship, increasing the myofilament calcium sensitivity [41, 55]. Conversely, reduced phosphorylation of MLC-2 results in a rightward shift of the force-pCa relationship [11,20].…”
Section: Discussionmentioning
confidence: 99%
“…183 In this model, constitutive increase in Ca 2+ sensitivity is associated with increased expression of NCX which might result in increased I NCX current to maintain Ca 2+ homeostasis during diastole when SERCA2a is also reduced. 184 Interestingly, this observation was noted in younger but not in older mice, reflecting the early age of onset of arrhythmias in TNNT2 -positive subjects. The reentry hypothesis is supported by evidence that TNNI3 mutations can increase spatial dispersion of activation times across the myocardium, thereby promoting reentry.…”
Section: Arrhythmias Caused By Heritable Defects In Calcium-handling mentioning
confidence: 94%